2007
DOI: 10.1007/s10549-007-9615-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of hormone therapy on E1S-sulfatase activity in non-malignant and cancerous breast cells in vitro

Abstract: Breast tissue possesses the enzymes for local estrogen biosynthesis. We measured the effect of Estradiol (E2), Tibolone (OrgOD14) and its metabolite Org4094 on estrone sulfate (E1S)-sulfatase (STS) using breast cancer (MCF-7) and non-malignant breast cells (HBL-100). Cells were cultured in 5% steroid depleted fetal calf serum for 3 days and subsequently incubated with each steroid for either 24 h or directly in cell extracts. STS mRNA and protein expression, and its subcellular localization were determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 66 publications
5
10
0
Order By: Relevance
“…Previous studies in BC cell lines have demonstrated that treatment with estradiol, and various progestins, respectively, rather affect enzyme activity than its protein levels and mRNA expression [40,59]. We previously reported similar effects in nonmalignant human breast cells in vitro [45]. Thus, the enzymatic effects leading to a decreased E 1 and E 2 formation could be mediated by a decreased STS, elevated sulfotransferase, or by a shift in the balance of 17␤-HSD type 1 and 2 activity.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies in BC cell lines have demonstrated that treatment with estradiol, and various progestins, respectively, rather affect enzyme activity than its protein levels and mRNA expression [40,59]. We previously reported similar effects in nonmalignant human breast cells in vitro [45]. Thus, the enzymatic effects leading to a decreased E 1 and E 2 formation could be mediated by a decreased STS, elevated sulfotransferase, or by a shift in the balance of 17␤-HSD type 1 and 2 activity.…”
Section: Discussionsupporting
confidence: 58%
“…STS activity was measured as described previously [45,46]. In brief, breast tissue (150 mg) was finely minced with scissors and homogenized on ice, in 2 ml 0.06 M Tris-HCl-buffer pH 7.0 (assay buffer throughout the entire procedure) for approximately 1 min at maximum speed using a Polytron homogenizer.…”
Section: E 1 S-sulfatase (Sts) Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that STS activity was higher in malignant than healthy cells and tissue, respectively, is in accordance with previous studies in breast cells [15] and brain tumors [17]. Other factors might also contribute to the differences observed such as species (human vs. monkey), origin of investigated material (SH-SY5Y cells obtained from bone marrow biopsy vs. hippocampus tissue obtained from brain necropsy), culture conditions (cells vs. tissue), and the hormonal environment.…”
Section: Discussionsupporting
confidence: 92%
“…STS activity was measured as described previously [15]. In brief, SH-SY5Y cells were homogenized on ice, in 2 ml 0.06 M Tris-HCl-buffer pH 7.0 (assay buffer throughout the entire procedure) for approximately 1 min at maximum speed using a Polytron® homogenizer (Kinematica, AG).…”
Section: E1s-sulfatase (Sts) Activity Assaymentioning
confidence: 99%